Automatic Backup Configuration of Routers using PERL Scripting - Don, Africa, Aaron; Richard, Mosqueda, Mark (International Journal of Engineering and Technology, 2018)
Network professionals are deeply challenged and interested with working on a large scale of network environment. The primary challenge to every professional is to maintain and manage a wide range of devices such as routers, switches, servers and firewalls. In line with maintaining a good infrastructure, doing a regular backup on each device is very essential. In the absence of backups, checks and updates of configuration shall be done manually for each of the relevant devices, which is unproductive and time consuming. In this study, automation is presented through a Perl script with Expect commands running on a Linux CentOS 7 accompanied by a MariaDB for the database. Upon running the script, information will be queried in the MariaDB and will thereof access the device to perform an automated backup that will be saved on the running operating system.Â